Teach yourself visually color knitting - Huff, Mary Scott (Teach yourself visually., 2012)
Are you a knitter looking to expand your knowledge and take on new challenges? Color adds vibrant, complex patterns to sweaters, hats, mittens, and more. For the uninitiated, color knitting can be intimidating, but it doesn't have to be. This book explains, step by step, the various methods and gives you a variety of projects so that you can put your newfound skills to use. Working with color--whether it's one richly toned variegated handspun yarn or multiple colors worked in an intricate pattern--is a great way to advance from basic projects to more complex and satisfying ones. Photo by photo, you'll learn all the techniques, including stripes, slip-stitch knitting, Fair Isle (stranded knitting), intarsia, and entrelac. Plus, you'll get some lessons on color theory and discover how to put together beautiful color combinations. It features 21 patterns using various colorwork skills, includes a stitch pattern dictionary for each technique and photos and detailed explanations that makes learning easy--